THE RELATIONSHIP OF FE ,ZINK (Zn), and VITAMIN A TO THE NEW STUDENTS OF ELEMENTARY SCHOOL’S NUTRIENT STATUS IN OUTSKIRTS OF KUPANG CITY, EAST NUSA TENGGARA PROVINCE - AGUSTINA SETIA; REGINA MARIA BORO (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
The lack of nutrient was happened because of the low of quality and quantity of nutrient supply, and because of infection also. Nutrient supply like vitamin A, Fe, and Zn are the components which influence someone’s nutrient status. The citizen of outskirts city usually identify by poverty. Vitamin A has a role in the mobilization of Fe reserve in human body to synthesize the hemoglobin. Fe and Zn which were given together can absorb well if Fe doses was not more than Zn. The research to new students of elementary school’s nutrient status in NTT Province in general, and in Kupang particularly was rare until now. To know nutrient status of new students of elementary school basically is important to keep up with the development of students’ study process as long as their education period in elementary school. To know the relationship of Zn, Fe, and vitamin A supply to the new students of elementary school’s nutrient status in outskirts of Kupang city, NTT Province. This is a quantity of research with observational design cross-sectional. The research will be done in Kupang City in 2 months. The populations of this research are 3993 students of class one at the elementary school (this populations counted according to the number of class one data on 2013, in Kupang City. It means that all of the elementary students in Kupang City were not included in this account). Minimum sample which was needed in this research were 98 students. To anticipate the drop out students, then needed to add 10%, so the number of sample which was needed in this research are 108 students. To take 108 students was used random sampling technique. The criteria of the sample are: the new elementary school students (not repeat students) on the time of measuring didn’t in sick condition and had not physic difference (hadn’t hunchbacked). Fe supply has a relationship to nutrient status (IMT/U) with p-value less than 0, 05 (p=0,019), Zn supply also point out the relationship to nutrient status (IMT/U) with p-value 0,038, and vitamin A has a relationship to new students of elementary school’s nutrient status with p-value 0, 005. There is a relationship between Fe supply with nutrient status (IMT/U), there is a relationship between Zn supply with nutrient status (IMT/U), there is a relationship between vitamin A supply with nutrient status (IMT/U). to the next researcher, besides measuring Fe supply, pay attention also macronutrient. Education organizer (school) need to pay attention to student’s nutrient problem, because the students who have nutrient problem tend to have problems on their ability to accept subject matter in class.